(3fXe GdeYdheGJ GdGOGQjI (B/s - (3ecdjhO, QGjehfOs; (3Tjd, LjhQL s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2006)
(3ebOeI dfXGe GdeYdheGJ GdeYJeO Ydi GdMGSH h GSJNOGe JbfjI GdeYdheGJ cejRI JfGaSjI h GSJNOGe JbfjI GdeYdheGJ aj GdONhd aj GdJLGQI GdGdcJQhfjI h cPdc GSJNOGe GdMGSH aj GdShb GdYGdej eY PcQ GdJVejfGJ GdGNdGbjI dJbfjI GdeYdheGJ h eaGgje GdfXe h efgLjGJ OhQI MjGI GdfXGe h CSGSjGJ JTZjd GdMGSH h bGYOI GdHjGfGJ h fXGe GOGQI bGYOI GdHjGfGJ h GJUGdGJ GdHjGfGJ h fXGe GdeYdheGJ GdeMGSHjI GVGaI Gdi fXGe GdeYdheGJ GdGOGQjI hfXe OYe GdbQGQGJ h GdecJH GdGaJQGVj h fXe eYdheGJ GdeTCI h fXe eYdheGJ efaPj GdGOGQI GdYdjG h cPG fXe eYdheGJ GdJShjb h fXGe eYdheGJ ehGQO GdeYdheGJ (B.s
(3eQGLY U(B.949, (3fdGMb U(B.825s
Keywords: (3GdGOGQIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s